THE USE OF NUMBERED HEADS TOGETHER TECHNIQUE WITH PICTURE TO IMPROVE READING COMPREHENSION OF THE TENTH GRADE OF SMKN 1 MAS UBUD 2019/2020 - D.A. Ayu Piradnyani; Ni Luh Putu Dian Sawitri; Putu Ayu Paramita D. (Jurnal Bakti Saraswati (JBS): Media Publikasi Penelitian dan Penerapan Ipteks, 2020)
Reading comprehension is about deriving meaning from connected texts. This skill should be taught in learning process to make the students enjoy learning English especially reading comprehension. The results of the pre-test showed that most of the subjects faced problem in reading comprehension. The subjects had difficulty in identifying general information, specific information, textual meaning, and textual reference of the text. The objective of the study was to find out whether or not reading comprehension of the tenth grade of SMKN 1 Mas Ubud in academic year 2019/2020 that consisted of 36 students can be improved through NHT Technique. Therefore, to achieve the objective of the present study, the researcher conducted a classroom action research. The research was done in two cycles and each cycle consisted of two sessions. Furthermore, the research instruments were analyzed by comparing the results of the pre-test and post-tests. The results of the post-test in each cycle clearly showed that there was significant improvement on the subjects’ reading comprehension. Besides, the subjects also gave positive responses on the implementation of NHT in the teaching reading comprehension. To sum up, the presents study concluded that reading comprehension of the tenth grade students of SMKN 1 Mas Ubud academic year 2019/2020 could be improved through NHT.